Vermiremediation of Saccharum officinarum Industrial Residues Using Eisenia fetida: Enhancing Vermicompost Biostability via Enzymatic Activity Profiling - Anto, Simi; Makeshwari, Uma (Journal of Research in Science and Engineering, 2025)
Jaggery is also known as gul, gud, gur, vellum and bella, It is a golden - yellow, dark brown, medicinally active, traditionally used and unrefined sugar. Fresh Bagasse was obtained from Mornisa Bio organics pvt. Ltd., MIDC, Chalisgaon. Trays that measured 58cm x 42cm were filled with 1kg mixture of the waste (Plant waste, cow dung, Sample, Earth worm, Cow dung, plant waste in the ratio 1: 1: 1: 1: 1:) to serve as test experiment. The 10 glass petri plates were use for this experimental assay. When we compare test sample of set A and Set B, the length of shoot and root was much more compare with control. In all this observation length of root and shoot is much more in sample 1 contains vermicompost obtained from mud sample & Bagasse.